DINAMIKA PERILAKU, EMOSIONAL, DAN INTERAKSI SOSIAL ANAK DENGAN AUTISME DI SEKOLAH DASAR KHUSUS NEGERI 01 KOTA SERANG - Risma Rahmawati; Yahdinil Firda Nadhira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Children with autism experience difficulties in behavior, emotional regulation, and social interaction that affect their learning process at school. This study aims to describe the dynamics of behavior, emotions, and social interactions of children with autism at Sekolah Dasar Khusus Negeri (SKhN) 01 Kota Serang. Using a qualitative approach with a case study design, the research involved two children with autism and one accompanying teacher. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model and validated through source and technique triangulation. The findings indicate that the children’s behavior is influenced by variations in communication ability and emotional control. Support from the accompanying teacher and a responsive environment plays a crucial role in enhancing positive emotional expression and social interaction. The application of adaptive learning strategies and teachers’ empathetic communication proved effective in reducing maladaptive behavior and increasing social participation in the classroom.